PENGARUH PENGURUSAN VISA ON ARRIVAL DI BANDAR UDARA SAM RATULANGI TERHADAP KEPUASAN WISATAWAN MANCANEGARA YANG DATANG DI SULAWESI UTARA - Agus Walansendow; Bet El Lagarense; Inggrid N. Tatara (Jurnal Ilmu Pariwisata, 2023)
World Tourism has become a human need throughout the world. Travelling activities continue to be carried out by millions of people in various countries with various backgrounds such as holidays, social or family activities, health, business, sports, conventions, education, and various reasons that encourage tourists to leave their places of residence for a while and visit the area or a country which is not their residence. However, before being able to enjoy the existing tours, tourists must have a visa issued by the destination country as a permit for someone to enter another country. Manado Class I Immigration Office is an agency that deals with tourist travelling documents, and is authorized to give decisions to Indonesian citizens or foreign nationals whether to travel or not. Manado Class 1 Immigration Office has 4 sections in it which really helps people to enjoy tourism and so on. One of the services provided is Visa on Arrival at Samratulangi Manado Airport. The study was intended to analyze, measure and explain the effect of obtaining a Visa on Arrival at Samratulangi Airport on the satisfaction of foreign tourists arriving in North Sulawesi. This research used observation, survey, and interview techniques. The analytical method used is Simple Linear Regression Analysis where the variable (X) is the processing of Visa on Arrival and the variable (Y) is international tourist satisfaction with the equation Y'=a+bX and correlation analysis is to calculate how strong the relationship is between the X and Y variables. The results the end of this study after calculating the simple linear regression analysis of the equation where Y' = 12.30 + 0.30X indicates the variable X (management of Visa on Arrival) will cause a change in the variable Y (satisfaction of foreign tourists) 0.30 and vice versa. The correlation coefficient (r) = 0.97 is close to 1 showing that there is a strong positive effect between variables X and Y and for the determinant coefficient (r2) = 88.52%, which indicates the effect of managing Visa on Arrival on foreign tourist satisfaction.